2023
DOI: 10.1039/d3ra00299c
|View full text |Cite
|
Sign up to set email alerts
|

Promising transition metal decorated borophene catalyst for water splitting

Abstract: Promising Ni metal decorated borophene catalyst for water splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…4 The appearance of different structures and the disclosure of their allotropes is influenced by the use of different methods/parameters of synthesis. 5 Envisioned by theorists 6,7 borophene is known for its high-temperature superconductivity, 8 metallicity, 9 excellent elastic strength, and electronic mobility, 10 making it a promising material for different applications such as an anode material in more powerful lithium-ion batteries, 11 catalytic capabilities, 12,13 and sensors. 14,15 The scientific community is excited about the extraordinary range of potential applications that borophene can be used for.…”
Section: Introductionmentioning
confidence: 99%
“…4 The appearance of different structures and the disclosure of their allotropes is influenced by the use of different methods/parameters of synthesis. 5 Envisioned by theorists 6,7 borophene is known for its high-temperature superconductivity, 8 metallicity, 9 excellent elastic strength, and electronic mobility, 10 making it a promising material for different applications such as an anode material in more powerful lithium-ion batteries, 11 catalytic capabilities, 12,13 and sensors. 14,15 The scientific community is excited about the extraordinary range of potential applications that borophene can be used for.…”
Section: Introductionmentioning
confidence: 99%
“…177 Based on density functional theory, it is found that Ni-and Pd-doped This journal is © the Owner Societies 2024 borophene sheets display advantageous catalytic activity toward the oxygen evolution reaction (OER), while Fe-, Co-, Cu-, Ru-, Rh-, Ag-, and Pt-doped borophene sheets can exhibit high catalytic activity toward the hydrogen evolution reaction (HER). 178,179 The free energies of the rate-determining step increase in the order of Co-= Fe-o Pd-o Pt-o Ni-o Rh-o Ru-o Ir-o Os-doped borophene. 180 From the results of theoretical studies, it is expected that the adsorption of H 2 and CO gases on pristine aluminene and H 2 gas on TM functionalized aluminene surfaces may show promise for its use as a reusable gas sensor and for gas storage with subsequent facile release.…”
Section: Doping Of Graphene (G)mentioning
confidence: 99%
“…The art of tailoring and creating materials with desired properties -materials engineering, includes techniques such as defect engineering [361][362][363], doping [44,362,[364][365][366][367][368][369], fluorinating [370] or alloy engineering [30][31][32][33][34]371] or salt engineering [35] by varying composition, strain engineering [11,16,26,36,170,[372][373][374] by applying mechanical load (such as hydro-static pressure [36,[375][376][377][378][379] or directional stress), and interfacial engineering [40,[42][43][44][45][46] by choosing different materials for forming interface with novel or exotic properties. These methods have been demonstrated to be very useful for tuning materials properties or creating new materials with advantageous properties.…”
Section: Coupling Of Data-driven Discovery With Traditional Techniquesmentioning
confidence: 99%